2008
DOI: 10.1097/01.aog.0000296657.41236.10
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Risk in Young Women With Polycystic Ovary and Polycystic Ovary Syndrome

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 19 publications
6
62
0
2
Order By: Relevance
“…Insulin values were expressed as SI units (1 mIU/ ml Z 6.945 pmol/L) [31]. C-peptide values were expressed as SI units (1 ng/ml Z 0.333 nmol/L) [32]. We performed pre-specified subgroup analyses by study quality and by menopausal status (postmenopausal only versus pre-and postmenopausal).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Insulin values were expressed as SI units (1 mIU/ ml Z 6.945 pmol/L) [31]. C-peptide values were expressed as SI units (1 ng/ml Z 0.333 nmol/L) [32]. We performed pre-specified subgroup analyses by study quality and by menopausal status (postmenopausal only versus pre-and postmenopausal).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…23 In the present study, women with PCOS had significantly higher Hcy levels than controls, which is similar to reports by some other investigators. [24][25][26][27][28][29][30] Mancini et al, have shown that no significant difference in Hcy levels in PCOS women and controls. 31 Hcy has a well-known role in cardiovascular morbidity and mortality and it has primary atherogenic and prothrombotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a very recent study, Battaglia et al (2010) demonstrated that young women with PCOS displayed levels of nitrite/nitrate within normal range and similar with those found in controls, which preserved the endothelium-dependent vasodilatation, which was also similar in both groups. There are also reports which, on the contrary, found lower levels of nitrites/nitrates in PCOS and subjects with polycystic ovaries (Battaglia et al, 2008) as well as in normal weight, eumenorrheic, nonhirsute daughters of patients with PCOS (Battaglia et al, 2009) compared with controls, which suggests that PCOS is a condition associated with an increased vascular risk.…”
Section: Endothelial Dysfunctionmentioning
confidence: 91%